Development of E-Book Media Based on the Book Creator Application to Improve the Effectiveness of Science Learning in Grade V of Nan Sabaris Elementary School - Marlina Marlina; Adriantoni Adriantoni; Hendrizal Hendrizal (Journal of Educational Sciences, 2026)
This research is motivated by the limited use of interesting and interactive digital learning media in science learning in grade V of Nan Sabaris Elementary School, thus impacting the effectiveness of the learning process and student learning outcomes. This study aims to develop an E-Book media based on the Book Creator application that is valid, practical, and effective for use in science learning. This research is a research and development (R&D) with stages of analysis, design, development, and evaluation. The results of the validity test showed a score of 85.00 for material experts, 90.00 for language experts, and 97.50 for media experts, all of which are in the very valid category. The practicality test by grade V teachers at SDN 17, SDN 15, and SDN 16 Nan Sabaris obtained an average score of 99.16% with a very practical category, while student responses showed very good results. The effectiveness test based on the N-Gain analysis showed values of 0.7694, 0.8000, and 0.7692 with a high category. Thus, Book Creator-based E-Books are suitable and effective for use in science learning in elementary schools.